The Influence of Corporate Culture and Compensation on Employees Commitment: The Role Of Satisfaction Work As Variables Intervening - Fakhruddin Siregar; Zulkifl Musannip Efendi Siregar; Nurintan Asyiah Siregar; Sumitro Sumitro; Hayanuddin Safri (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2023)
This research aims to analyze the influence of company culture and compensation To Commitment Work Dano Permai Housing Employees: The Role of Satisfaction Work As Variable Intervening . This type of research is quantitative research and the respondents for this research as a sample are Dano Permai Housing in Labuhanbatu Regency with 40 employees . The data analysis method uses Partial Least Square (PLS) with smartPLS software . Research shows that company culture has a positive effect on employee work commitment , compensation has a positive effect on employee work commitment , company culture and compensation have a positive effect on employee work commitment through job satisfaction as an intervening variable Keywords: Company Culture, Compensation, Work Commitment, Job Satisfaction